Bryophyte flora of cemeteries in the City of Novi Sad (Serbia) - Milovanović, Ankica; Vukov, Dragana; Igić, Ružica; Šikuljak, Tijana; Ćuk, Mirjana; Ilić, Miloš (Biologia Serbica, 2023)
This study analyzes the bryophyte flora of six old cemeteries in Novi Sad and reports on the findings of the first study on bryophytes in Novi Sad. All investigated cemeteries are more than a hundred years old and are protected by the Institute for Protection of Cultural Monuments of Novi Sad. A total number of 49 bryophyte species was recorded. Although urban habitats are different from native habitats, bryophytes can still survive successfully. The study sheds light on the importance of cemeteries as urban habitats for bryophytes, and highlights the need for further research in this area.